(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
A failure to develop language is one of the earliest signs of autism. Some children with ASD may not be able to communicate using speech or language, and some may have very limited speaking skills. As the focal point of this paper is on the language impairments of the autistic children, much attention will not be paid on the medical and neurological side of autism. In this study, the researchers used the mixed method approach as the research design — Methodological triangulation: use of two or more research methods in a single study. There are variations for the use of this method. The participants of the study is composed of students diagnosed with autism spectrum disorder from both genders (male and female). In terms of the language impairments in the sound development, some students with autism have backed phonemes, labialized and prolonged phonemes, and palatalized phonemes. In terms of morphology particularly on repetition of new words, omission and alteration are present among the students with autism. In terms of the non-verbal token ratio, due to the limited use of words, it is evident that there are words omitted in the sentences. Some of the participants, intended to imitate the words they hear so that they can utter it. When a child has both a language-based disorder and ASD, these difficulties can be amplified. Additionally, most academic subjects rely heavily on the use of language for instruction, so learning in all areas of study will likely be affected by a language disorder. It is but appropriate for the institutions to develop a learning manual or module intended for the students with autism specifically with the problems encountered herewith to augment the process of enhancement of the learning experiences of the students, eventually create a wonderful learning experiences.